Bioluminescence of the tropical Indian Ocean: a multiple‐scale variation. (28th June 2022) - Piontkovski, Sergey A.; Melnik, Alexandr V.; Serikova, Irina M.; Evstigneev, Vladislav P.; Dobretsov, Sergey
Abstract: Large‐scale surveys represented by 5800 bathymetric casts in the western Indian Ocean (0–22 o N, 54–58 o E), elucidated the 10‐fold variation of the bioluminescent potential (BP) in the upper mixed layer, during the winter (north‐east) monsoon season. The mesoscale survey in February 2017 consisted of 26 drift stations (4 o N–3 o S, 65–68 o E) on which 5–10 bathymetric casts were deployed down to 60 m. The maximal BP was associated with the periphery of a cyclonic eddy. The two‐fold to three‐fold variation of BP characterized the spatial heterogeneity modulated by a detected eddy. High‐frequency casts on drift stations resembled the fine‐scale heterogeneity in which the three‐fold variation was observed within the BP maximum at a 37 ± 13 m depth. The latter one was located above the deep chlorophyll maximum at a 80 m depth. A general decline of the BP variance from the large scale through mesoscale to fine scale, fits that of the zooplankton biomass. Abstract : Field surveys of a stimulable bioluminescence onboard research vessels implied the 10‐fold variation of the intensity on the scale of the western Indian Ocean. The three‐fold variation of the bioluminescence intensity characterized the mesoscale spatial heterogeneity modulated by a cyclonic eddy that was well pronounced in the temperature field. The bioluminescence maxima were located on the northern and southern eddy periphery. High frequency casts on drift stations resembled the fine‐scale heterogeneity in which the three‐fold variation was observed.